Cytotoxic effects of single and binary mixtures of metal oxide nanoparticles and metal(loid) on A549 human cell line. - Rosário, Fernanda (2021)
Background, Motivation and Objective: The need to assess the toxicity resulting from exposure to mixtures of chemicals has been recognized by the WHO and EU, as humans are simultaneously exposed to an array of natural and anthropogenic contaminants. Of particular interest are the potential combined effects resulting from interaction of nanoparticles (NPs) and metals. While the first are the current driving force for emerging contaminants, the latter, as legacy contaminants, remain a concern. Metals show strong affinity to NPs, which can change the uptake and toxicity to the organism of each individual contaminant. Studying the effects on the respiratory tract is of upmost relevance because of its constant contact with xenobiotics, resulting in adverse effects on the lung. Considering the above, the objective of this work was to assess and compare viability, cell cycle, and uptake of A549 cells after exposure to single and binary mixtures of titanium dioxide nanoparticles (TiO2NP), cerium oxide nanoparticles (CeO2NP), arsenic (As) and mercury (Hg). These chemicals were chosen because: 1) TiO2NP are among the most abundantly used NPs; 2) CeO2NP have been used in nanomedicine for its high biocompatibility and cytoprotective effect; and 3) As and Hg due to their non‐biodegradable, persistent, and extremely toxic character. This work intends to support adequate human risk assessment resulting from co-exposure to multiple contaminants.